2020
DOI: 10.1038/s41467-020-16618-6
|View full text |Cite|
|
Sign up to set email alerts
|

Pericyte FAK negatively regulates Gas6/Axl signalling to suppress tumour angiogenesis and tumour growth

Abstract: The overexpression of the protein tyrosine kinase, Focal adhesion kinase (FAK), in endothelial cells has implicated its requirement in angiogenesis and tumour growth, but how pericyte FAK regulates tumour angiogenesis is unknown. We show that pericyte FAK regulates tumour growth and angiogenesis in multiple mouse models of melanoma, lung carcinoma and pancreatic B-cell insulinoma and provide evidence that loss of pericyte FAK enhances Gas6stimulated phosphorylation of the receptor tyrosine kinase, Axl with an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 51 publications
(56 reference statements)
1
33
0
Order By: Relevance
“…Mechanistically, the loss of pericyte FAK enhanced the expression of the proangiogenic and tumorigenic cytokine Cyr61, via a Gas6/Axl axis, driving tumour progression. These results were corroborated by human melanoma studies, where a high correlation was shown between tumour size and loss of pericyte-FAK [ 19 ]. As in ECs, pericyte FAK phosphorylation appears to have distinct roles in tumour growth and angiogenesis.…”
Section: Adhesome Function In Vasculaturesupporting
confidence: 65%
See 1 more Smart Citation
“…Mechanistically, the loss of pericyte FAK enhanced the expression of the proangiogenic and tumorigenic cytokine Cyr61, via a Gas6/Axl axis, driving tumour progression. These results were corroborated by human melanoma studies, where a high correlation was shown between tumour size and loss of pericyte-FAK [ 19 ]. As in ECs, pericyte FAK phosphorylation appears to have distinct roles in tumour growth and angiogenesis.…”
Section: Adhesome Function In Vasculaturesupporting
confidence: 65%
“…Recent studies using genetic deletion approaches have addressed the role of mural FAK in tumour angiogenesis and cancer development. In particular, mural FAK deficiency enhanced tumour growth and angiogenesis in syngeneic subcutaneous mouse models and spontaneously arising RIP-Tag2 pancreatic tumours [ 19 ]. In both models, FAK deficiency weakened the association of pericytes with tumour blood vessels and increased tumour angiogenesis.…”
Section: Adhesome Function In Vasculaturementioning
confidence: 99%
“…Our data demonstrate that FAK-Y861F pericytes decrease tumour burden, at least in part, by directly affecting tumour cell apoptosis, and call for further consideration of the role of tumour pericytes in the direct control of tumour growth, in addition to their effects on vessel stabilisation. Indeed, we have recently shown that pericytes play a central role in the control of primary tumour growth, through cross-talk with multiple cell types in the tumour microenvironment [19,20]. FAK is upregulated in many cancer types and is currently being targeted as a potential anti-cancer agent because of its essential roles in tumour growth and angiogenesis [12,[32][33][34].…”
Section: Discussionmentioning
confidence: 99%
“…More recently, we have shown that non-phosphorylatable mutations of tyrosines 397 and 861 (Y397 and Y861) in endothelial cells have differential effects on tumour angiogenesis [17] and that endothelial cell FAK regulates angiocrine signalling in the control of doxorubicin sensitivity in malignant cells [18]. Whilst FAK has been studied extensively in endothelial cells, the function of FAK in pericytes during tumour growth and angiogenesis is starting to emerge, with loss of pericyte FAK enhancing tumour angiogenesis [19]. Given that pericytes are an important cell type in the regulation of tumour growth and paracrine signalling [20][21][22], here we have examined the role of FAK point mutations in pericytes during pathological angiogenesis.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, the deletion of endothelial FAK in vivo reduced the vascular–endothelial growth factor (VEGF)-dependent neovascularization and inhibited the tumor growth and angiogenesis in adult mouse models [ 166 ]. Endothelial FAK has also been involved in the resistance to both irradiation and DNA-damaging therapies and in the dysregulated cross-talk between ECs and pericytes that may lead to the instability of the tumor microvasculature and influence the tumor growth [ 167 , 168 ].…”
Section: Fak and The Breast Tmementioning
confidence: 99%